Postnatal hyperoxia or DEHP exposure leads to growth restriction and delayed lung development in newborn rats - Zhong-Jie Liang; Qiu-Ping Wu; Bei-Tao Chen; Zhen-lang Lin; Jing Lin; Shang-Qin Chen (Elsevier, 2018)
Background: Di-(2-ethylhexyl) phthalate (DEHP) is commonly used as a plasticizer in many medical devices. We previously showed that maternal DEHP exposure led to restricted growth and delayed lung maturation in newborn rats. As oxygen toxicity continues to be a major risk factor for bronchopulmonary dysplasia, the aim of this study was to examine the effect of hyperoxia, DEHP or DEHP combined with hyperoxia on the growth and lung maturation of newborn rats. Methods: Newborn rats received DEHP injection, hyperoxia exposure or DEHP injection combined with hyperoxia exposure for one week or two weeks. A control group received an equal volume of vehicle and was maintained in room air. Results: Hyperoxia and hyperoxia + DEHP exposure for one week led to growth failure in newborn rats. Pups in the hyperoxia group showed catch-up growth after being maintained in room air for an additional 7 days but this was not the case with the latter group, which continued to receive DEHP. Hyperoxia and DEHP both delayed lung development, as evidenced by decreased radial alveolar count. Quantitative RT-PCR showed that hyperoxia decreased the transcripts of VEGF, VEGFR-2 and eNOS on days 7 and 14, and DEHP exposure alone also led to decreased expression of VEGF gene in 14-day-old rat pups. Conclusion: Postnatal hyperoxia and/or DEHP exposure lead to growth restriction and delayed lung alveolar development. The VEGF gene expression was altered and may be involved as one of the possible molecular mechanisms.